A novel methodology for the path alignment of visual SLAM in indoor construction inspection - Lu, Tao; Tervola, Sonja; Lü, Xiaoshu; Kibert, Charles J.; Zhang, Qunli; Li, Tong; Yao, Zhitong (Elsevier, 2021)
Path alignment is the process of mapping an indoor construction inspection path reconstructed by a visual SLAM system onto a 2D map with user interaction required to pinpoint at least two common tie points. In practice, more points are often needed due to path distortions and linear transformations, potentially resulting in reduced productivity. This paper proposes a methodology that combines two novel algorithms for the path alignment: (1) PCA_STAN_ALGO applies principal component analysis to remove path distortions caused by the xz plane of a camera coordinate system not being parallel to the floor plane; and (2) GRPX_TRANS utilizes a graphical user interface to facilitate the path alignment. The proposed methodology enables the users to utilize just two tie points for successful path alignment. An experimental study showed that applying both PCA_STAN_ALGO and GRPX_TRANS saved about 50% in time compared to using only GRPX_TRANS, a result of needing minimal moving points.
Keywords: Principal component analysis; Simultaneous localization and mapping; Path alignment; Affine transformation; Path distortion; 2-Point Scheme; fi=Energiatekniikka|en=Energy Technology|